DETERMINANTS OF FINANCIAL PERFORMANCE EVALUATION IN SMALL AND MEDIUM ENTERPRISES - Hamzah, Amir; Rahmawati, Teti; Fitriani, Chintia; Febriansyah, Yudi (Faculty of Economics and Business University of Mataram, 2024)
This study analyzes factors influencing the financial performance of small and medium enterprises (SMEs), addressing the limited research that focuses on specific variables in the SME context. It examines the effects of mental accounting, financial record-keeping, financial literacy, financial management, and digital accounting on SME financial performance. Using Structural Equation Modeling (SEM), data from 216 SMEs in Kuningan Regency were analyzed. The findings reveal that financial record-keeping, financial literacy, and financial management significantly and positively impact SME financial performance. Conversely, In contrast, mental accounting has a significant negative impact, while digital accounting does not significantly affect financial performance. These results suggest that effective financial management practices can enhance financial performance, while improper use of mental accounting and ineffective implementation of digital accounting may hinder it. This research implies the need to improve financial literacy, adopt more effective financial management practices, and provide digital accounting training to help SMEs overcome financial challenges.